To determine:

Graph of \(y=sqrt(x−2)−1\) by applying appropriate transformation.

Firstly, we will draw graph of \(y=sqrtx\) which is given by:Y1

now, we will draw graph of \(y=sqrt(x−2)\) by shifting the graph of \(y=sqrtx\) two units towards right.

So, the graph of \(y=sqrt(x−2)\) is as follows:Y2

Now, we will draw graph of \(y=sqrt(x−2)−1\) by shifting the graph of \(y=sqrt(x−2)\) one unit downward along y axis.

The graph of \(y=sqrt(x−2)−1\) is given by:Y3

Graph of \(y=sqrt(x−2)−1\) by applying appropriate transformation.

Firstly, we will draw graph of \(y=sqrtx\) which is given by:Y1

now, we will draw graph of \(y=sqrt(x−2)\) by shifting the graph of \(y=sqrtx\) two units towards right.

So, the graph of \(y=sqrt(x−2)\) is as follows:Y2

Now, we will draw graph of \(y=sqrt(x−2)−1\) by shifting the graph of \(y=sqrt(x−2)\) one unit downward along y axis.

The graph of \(y=sqrt(x−2)−1\) is given by:Y3